2020
DOI: 10.4055/cios.2020.12.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Standard versus an Accelerated Ponseti Protocol for Clubfoot: A Prospective Randomized Study

Abstract: Congenital clubfoot, or congenital talipes equinovarus (CTEV), is one of the most common congenital deformities. 1) It most likely represents congenital dysplasia of all musculoskeletal tissues (musculotendinous, ligamentous, osteoarticular, and neurovascular structures) distal to the knee. This conclusion is based on multiple investigators' observations of a myriad of different abnormal anatomic findings and on the functional outcome of patients who were believed to have received optimal non-operative or oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In the study by Islam et al, they compared the scores of groups using both the Pirani and Dimeglio classifications. On the other hand, in the study by Aydin et al, figures are shown comparing the Pirani results at beginning of the Ponseti method and after Achilles tendon tenotomy, showing that there was an improvement in the patients [ 3 , 5 , 6 , 8 , 13 ].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the study by Islam et al, they compared the scores of groups using both the Pirani and Dimeglio classifications. On the other hand, in the study by Aydin et al, figures are shown comparing the Pirani results at beginning of the Ponseti method and after Achilles tendon tenotomy, showing that there was an improvement in the patients [ 3 , 5 , 6 , 8 , 13 ].…”
Section: Discussionmentioning
confidence: 97%
“…It is approximately three times more frequent in males than in females. Clubfoot is present unilaterally or bilaterally in 50% of cases [ 2 , 5 , 6 , 7 , 8 ]. Its etiology may be associated with myelodysplasia, arthrogryposis or multiple congenital deformities, but the most common presentation is in isolation, which is considered the idiopathic type [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations